Multidimensional analysis reveals environmental factors that affect community dynamics of arbuscular mycorrhizal fungi in poplar roots - Han, Shuo; Wang, Xia; Cheng, Yao; Wu, Guanqi; Dong, Xiaoyi; He, Xiangwei; Zhao, Guozhu (Frontiers in Plant Science, 2023)
Poplar is a tree species with important production and application value. The symbiotic relationship between poplar and arbuscular mycorrhizal fungi (AMF) has a key role in ecosystem functioning. However, there remain questions concerning the seasonal dynamics of the AMF community in poplar roots, the relationship between AMF and the soil environment, and its ecological function. Poplar roots and rhizosphere soil were sampled at the end of April and the end of October. The responses of AMF communities to season, host age, and host species were investigated; the soil environmental factors driving community changes were analyzed. The diversity and species composition of the AMF community were higher in autumn than in spring. Season, host age, host species, and soil environmental factors affected the formation of the symbiotic mycorrhizal system and the AMF community. Differences in the communities could be explained by soil pH, total nitrogen, total phosphorus, total potassium, available potassium, and glomalin content. The AMF community was sensitive to changes in soil physicochemical properties caused by seasonal dynamics, particularly total potassium. The change in the mycorrhizal symbiotic system was closely related to the growth and development of poplar trees.